Capital and society: theoretical and empirical approaches - Fernández Llanos, Miguel (MAD, 2004)
<!--[if gte mso 9]> Normal 0 21 false false false ES-TRAD X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->Under capital concept lies multiple meanings undercovered result of multiple semantic references that have the concept. This work will attempt to prove that capital, collecting the distinctions at the present day that provide it, become to the mechanism that make possible the structural coupling among interactions and functional systems and whose evolution run in parallel to the society's evolution established a theoretical passing through, with diverse empirical manifestations, between the differentiation and integration of society. It is posible in view the intrincate relationships that establish the communicative mechanism capital with generalized symbolic communication media, features that allow design general communicative frameworks of intersystemical relationships, allow likewise that will named communication assymetry.